Hardly Ever Otherwise - Matios M.; Matios Maria; Tkacz Yuri (Melbourne Bayda Books, 2010)
Everything eventually reaches its appointed place in time and space. Maria Matios's dramatic family saga, Hardly Ever Otherwise, narrates the story of several western Ukrainian families during the last decades of the Austro-Hungarian Empire, and expands upon the idea that "it isn't time that is important, but the human condition in time." In Matios's multi-tiered plot, the grand passions of ordinary people are illuminated under the caliginous light of an ethereal mysticism. Digressions on love, envy, transgression, together with atonement are woven into the story. Each character in this outstanding drama has an irrefutable alibi, a unique truth, and a private conflict with honor and duty. Her characters do not always act in accordance with logic and law books, as the laws of honor clash with the laws of the heart. And this is why it is hardly ever otherwise.
Keywords: 82-3 (NhUDOVNQ PROZAs